2023
DOI: 10.1002/eom2.12385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvation shell structure on thermopower of liquid redox pairs

Abstract: Developing redox electrolytes with high thermopower is the key to making efficient thermogalvanic batteries for harvesting low‐grade heat. This work applies molecular dynamics simulations to predict the thermopower (i.e. thermogalvanic temperature coefficient) of the redox pairs Fe(CN)63−/Fe(CN)64− and Fe3+/Fe2+, showing excellent agreement with experimental values. We showed that of the Fe3+/Fe2+ redox pair can be increased from 1.70.4 mV/K to 3.80.5 mV/K with the increased acetone to water fraction. We dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…(i) Methods of predicting the Soret and thermogalvanic thermopower are in urgent demand for the development of high-thermopower i-TE materials but remain highly challenging due to the complicated and long-range features of ion−ion and ion−solvent interactions. Although recent MD simulations have been applied to predict S tg of Fe 3+ /Fe 2+ and Fe(CN) 6 3− / Fe(CN) 6 4− redox pairs, 98 it is only applicable to a dilute solution of simple redox pairs and cannot predict thermopower of redox reactions involving chemical species from the electrodes. A computational framework for studying S td in complex electrolytes (e.g., polyelectrolytes, ionic liquids, and gels) is still lacking.…”
Section: ■ Summary and Outlookmentioning
confidence: 99%
“…(i) Methods of predicting the Soret and thermogalvanic thermopower are in urgent demand for the development of high-thermopower i-TE materials but remain highly challenging due to the complicated and long-range features of ion−ion and ion−solvent interactions. Although recent MD simulations have been applied to predict S tg of Fe 3+ /Fe 2+ and Fe(CN) 6 3− / Fe(CN) 6 4− redox pairs, 98 it is only applicable to a dilute solution of simple redox pairs and cannot predict thermopower of redox reactions involving chemical species from the electrodes. A computational framework for studying S td in complex electrolytes (e.g., polyelectrolytes, ionic liquids, and gels) is still lacking.…”
Section: ■ Summary and Outlookmentioning
confidence: 99%
“…Such a property affects the dynamics of water molecules and thereby the hydrogen bond network in the electrolyte . Recent atomistic simulations revealed that the hydration entropy change is highly related to the solvent dipole orientations, which provides microscopic insights into electrolyte design with high α . Overall, it is considered that there is a specific anion effect on α associated with the solvation structure variation and ion–water interactions …”
mentioning
confidence: 99%
“…Considering the combined effects of Δ S e,1 , Δ S s , and Δ S e,2 , the total entropy change follows the order of SO 4 2– < Cl – < NO 3 – < ClO 4 – , the reverse order of the Hofmeister series, resulting in the observed variation trend of α. The mechanism can be further investigated from a microscopic perspective with the help of atomistic simulations on the hydration shell structures at the molecular level. , …”
mentioning
confidence: 99%
See 2 more Smart Citations